Belowground competition for nutrients in shrub-encroached Mediterranean dehesas - Rivest, David; Rolo, Víctor; López-Díaz, M Lourdes; Moreno, Gerardo (Nutrient Cycling in Agroecosystems, 2011)
Managing multilayered silvopastoral systems such as Mediterranean dehesas requires the study of nutrient resource partitioning among coexisting species and determination to what extent soil nutrients are limiting plant growth. We determined the effects of NPK fertilisation maintained over two consecutive years on dry matter production and nutritional status of pasture (herbaceous) species, two shrub species and Quercus ilex L. in two silvopastoral sites with different shrub-layer species. We selected two prominent Mediterranean shrub species that vary in their speciﬁc ecological strategies: a N2-ﬁxing and sparse deep-rooting shrub (Retama sphaerocarpa (L.) Boiss, Retama site), and a dense shallow-rooting shrub (Cistus ladanifer L., Cistus site). Fertilisation signiﬁcantly (P B 0.05) increased pasture dry mass by 460% and 1,090% in the Retama and Cistus sites, respectively. Nitrogen uptake by pasture species was most stimulated in both sites, and was the major limiting nutrient for this group. At the Cistus site, fertilisation signiﬁcantly increased leaf dry mass of Q. ilex by 53%, but no signiﬁcant effect was found at the Retama site. There were no signiﬁcant effects of fertilisation treatments on dry mass and nutrient status of Retama cladodes and Cistus leaves. Vector analysis revealed that the magnitude of relative changes in nutrient uptake and dry matter production of pasture in response to fertilisation was markedly higher than that of Q. ilex, R. sphaerocarpa and C. ladanifer, suggesting high competitive ability of pasture species for soil nutrients. Results suggest that patterns of soil nutrient partitioning are site-speciﬁc and, thus, likely depend on the dominant species in the shrub layer
Keywords: Cistus ladanifer; Dry matter production; Native pasture; Nutrient uptake; Quercus ilex; retama sphaerocarpa; Silvopastoral systems